Effect of labetalol and lignocaine on hemodynamic response to laryngoscopy and endotracheal intubation - Baby Rani, Hanumanla; Yamini, Chikkam (ScienceRise: Medical Science, 2023)
Direct laryngoscopy and endotracheal intubation is a noxious stimuli and induce sympathomimetic responses. Although well tolerated in healthy subjects, it may impose life-threatening arrhythmias, left ventricular failure or rupture of cerebral aneurysm in susceptible patients. The aim is to study the effects of intravenous labetalol and lignocaine on haemodynamic responses to laryngoscopy and endotracheal intubation. Materials and methods: It is a cross-sectional and randomized controlled study with two study groups was planned. 70 patients were randomly assigned to one of two groups: those receiving Labetalol 0.25 mg/kg (n=35) or those receiving lignocaine 1mg/kg (n=35). The parameters assessed are heart rate, systolic BP, diastolic BP and Mean arterial pressure. Baseline parameters were recorded at the time of induction, post-intubation immediately and 1, 3, 5, 10 minutes later. Results: In the current study, at the time of induction, the mean heart rate was 65.97 ± 5.22 per min in group LB whereas the mean heart rate was 76.66 ± 8.49 per min in group LG which was statistically significant (P value <0.001). There was significantly reduced systolic blood pressure at 1min after intubation, 3min after intubation, 5min after intubation, and 10min after intubation in patients of group LB when compared with patients of group LG (P value <0.05). Significantly reduced diastolic blood pressure at 1 min after intubation, 3 min after intubation, 5 min after intubation, and 10 min after intubation in patients of group LB when compared with patients of group LG (P value <0.05). Conclusions: It was concluded in the present study that intravenous labetalol of dosage 0.25 mg/kg before laryngoscopy and endotracheal intubation was efficient in attenuating the hemodynamic parameters